1995
DOI: 10.1177/019459989511200407
|View full text |Cite
|
Sign up to set email alerts
|

Tonsil lymphoma presenting as tonsillitis after bone marrow transplantation

Abstract: Bone marrow transplantation for the treatment of leukemia is increasingly successful in rendering patients disease free. However, it has become evident that the associated severe immunosuppression predisposes this population to an increased risk for other neoplastic disorders. We report on six patients in whom non-Hodgkin's lymphoma of the tonsillar region developed within 5 months after T-cell-depleted bone marrow transplantation for the treatment of leukemia at Memorial Sloan-Kettering Cancer Center from Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…PTLD often presents in the region of Waldeyer's ring as ATH. [4][5][6][7]12 In a recent retrospective study of children having undergone liver transplantation over a 14-year period (1984 to 1998), 39% of those who underwent adenotonsillectomy for airway obstruction or asymptomatic tonsillar enlargement were noted to have EBV-related hyperplasia in the adenotonsillar tissue. 13 Given the high incidence of EBV-related hyperplasia, we feel strongly that even asymptomatic ATH should be surgically addressed in this population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PTLD often presents in the region of Waldeyer's ring as ATH. [4][5][6][7]12 In a recent retrospective study of children having undergone liver transplantation over a 14-year period (1984 to 1998), 39% of those who underwent adenotonsillectomy for airway obstruction or asymptomatic tonsillar enlargement were noted to have EBV-related hyperplasia in the adenotonsillar tissue. 13 Given the high incidence of EBV-related hyperplasia, we feel strongly that even asymptomatic ATH should be surgically addressed in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the clinical significance of such hypertrophy in the immuno‐suppressed patient is not entirely clear. However, previous studies have demonstrated that ATH in the pediatric posttransplant population can represent PTLD 3–7 . Therefore, we sought to evaluate a large population of pediatric transplant recipients, focusing on signs and symptoms of ATH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our series, TL developed in previously healthy children. It has been reported to occur as a second malignancy, 12 and in association with immunosuppression following bone marrow 13 and heart transplantation. 14 Abnormalities of the tonsils should clearly be regarded with great suspicion in the transplant population.…”
Section: Discussionmentioning
confidence: 99%
“…On review of the literature, we found several isolated anecdotal case reports of unsuspected diagnoses in routine T%A specimens. As one might expect, the most common diagnosis was lymphoma, 4–8 but other diagnoses included but were not limited to Epstein‐Barr virus lymphoproliferative disorder, 9 Langerhans' cell histiocytosis, 10 pemphigus vulgaris, 11 teratoma, 12 rhabdomyosarcoma, 13 and sarcoidosis 14…”
Section: Discussionmentioning
confidence: 99%